The many faces of SIRT6 in the retina and retinal pigment epithelium - Cheng, Jie; Keuthan, Casey J.; Esumi, Noriko (Frontiers in Cell and Developmental Biology, 2023)
Sirtuin 6 (SIRT6) is a member of the mammalian sirtuin family of NAD+-dependent protein deacylases, homologues of the yeast silent information regulator 2 (Sir2). SIRT6 has remarkably diverse functions and plays a key role in a variety of biological processes for maintaining cellular and organismal homeostasis. In this review, our primary aim is to summarize recent progress in understanding SIRT6’s functions in the retina and retinal pigment epithelium (RPE), with the hope of further drawing interests in SIRT6 to increase efforts in exploring the therapeutic potential of this unique protein in the vision field. Before describing SIRT6’s role in the eye, we first discuss SIRT6’s general functions in a wide range of biological contexts. SIRT6 plays an important role in gene silencing, metabolism, DNA repair, antioxidant defense, inflammation, aging and longevity, early development, and stress response. In addition, recent studies have revealed SIRT6’s role in macrophage polarization and mitochondrial homeostasis. Despite being initially understudied in the context of the eye, recent efforts have begun to elucidate the critical functions of SIRT6 in the retina and RPE. In the retina, SIRT6 is essential for adult retinal function, regulates energy metabolism by suppressing glycolysis that affects photoreceptor cell survival, protects retinal ganglion cells from oxidative stress, and plays a role in Müller cells during early neurodegenerative events in diabetic retinopathy. In the RPE, SIRT6 activates autophagy in culture and protects against oxidative stress in mice. Taken together, this review demonstrates that better understanding of SIRT6’s functions and their mechanisms, both in and out of the context of the eye, holds great promise for the development of SIRT6-targeted strategies for prevention and treatment of blinding eye diseases.